SPATIAL PLANNING POLICY STRATEGY IN THE DEVELOPMENT OF TANJUNGBALAI CITY AREA - Sri Handayani Saragih; Cut Nuraini; Abdi Sugiarto (PT. Radja Intercontinental Publishing, 2025)
Spatial planning is one of the important elements in sustainable regional development, especially for developing cities such as Tanjungbalai City. This study aims to identify the existing conditions of spatial planning in Tanjungbalai City and to propose policy strategies that can improve the quality of spatial planning in regional development. The results of the study indicate that Tanjungbalai City faces various challenges in implementing spatial planning policies, such as lack of coordination between agencies, limited human resources, and inconsistencies between plans and realities in the field. To overcome this, a more integrated, participatory, and data-based policy is needed. The recommended strategies include strengthening coordination between agencies, increasing community participation, using technology in supervision, and developing equitable and sustainable infrastructure. The implementation of effective spatial planning policies will support the achievement of structured, sustainable regional development and provide social and economic benefits for the people of Tanjungbalai City.